2001
DOI: 10.4067/s0717-71782001000200005
|View full text |Cite
|
Sign up to set email alerts
|

Estructura de longitud y relación longitud-peso en besugo (Epigonus crassicaudus), en la zona centro-sur de Chile

Abstract: RESUMEN. Se analiza temporal y espacialmente las distribuciones de frecuencias de longitud y la relación longitudpeso, con registros obtenidos en las capturas de besugo efectuadas por la flota arrastrera industrial de la zona centrosur de Chile. El estudio cubrió el área comprendida entre Punta Curaumilla (33º10S) y sur de isla Mocha (38º38S), de octubre de 1998 a septiembre de 1999. Los principales resultados indican que la distribución de frecuencias de longitud del recurso es principalmente de carácter unim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is important to note that in previous studies using whole sagittal otolith readings, the estimated maximum age was ~15 years (e.g. Gálvez et al ., 2000; Cubillos et al ., 2009). Conversely, in the current study, on average, 59 rings in older fish were identified, with a maximum age of 67 years, using transversal sections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that in previous studies using whole sagittal otolith readings, the estimated maximum age was ~15 years (e.g. Gálvez et al ., 2000; Cubillos et al ., 2009). Conversely, in the current study, on average, 59 rings in older fish were identified, with a maximum age of 67 years, using transversal sections.…”
Section: Discussionmentioning
confidence: 99%
“…To date the age determination for this species has been somewhat controversial. Previous studies using whole otoliths produced zone count readings which resulted in maximum age being estimated as 15 years (Gálvez et al ., 2000; Cubillos et al ., 2009; Contreras-Reyes & Arellano-Valle, 2013). In contrast, Ojeda et al .…”
Section: Introductionmentioning
confidence: 99%